Vision loss, tractional retinal detachment, and profound anemia due to rectal carcinoma - Yamamoto, Akira (Clin Case Rep, 2020)
Profound anemia can cause severe proliferative retinopathy and tractional retinal detachment; therefore, it is important to closely investigate the cause of anemia. Endoscopy and computed tomography are valuable tools for this purpose.